Beethoven Monument in Bonn - Kollarz, Franz (artist):::Creator::::::::::::; Hofmann, E. (photographer):::Contributor::::::::::::; Hähnel, Ernst Julius, 1811-1891 (sculptor):::Contributor::::::::::::
Image of the Beethoven monument in Bonn sculpted by Ernst Julius Hähnel clipped from an unidentified German-language newspaper